Ocean warming enhances iron use efficiencies of marine ammonia-oxidizing archaea - Wei Qin; Alessandro Tagliabue; Lei Hou; Min Xu; Xiaopeng Bian; Dawn M. Moran; Duo Zhao; Qian Li; Matthew R. McIlvin; Yue Zheng; Shuh-Ji Kao; Yao Zhang; et al. (Proceedings of the National Academy of Sciences, 2026)
Ammonia-oxidizing archaea (AOA) are among the most abundant microorganisms in the ocean, playing a fundamental role in the marine nitrogen cycle. Although temperature and trace metal availability each individually influence the growth and activity of marine AOA, there is only a very limited understanding of the interactive effects of these two major factors on AOA in the rapidly changing ocean. Here, we show that the iron requirements of the model marine AOA species Nitrosopumilus maritimus SCM1 are highly sensitive to temperature changes. A 5 °C increase in growth temperature reduced SCM1 iron requirements by >80%, and was associated with a substantial increase in iron use efficiencies (IUE, mol C fixed/h/mol cellular Fe) under iron-limited and warming conditions. A thermally enhanced IUE enables SCM1 to more efficiently utilize scarce available iron supplies to support its growth. Whole-cell proteomic analysis revealed that iron limitation decreased expression of a ferredoxin and increased expression of a copper-dependent plastocyanin that became more pronounced with warming, suggesting coordinated electron transport response regulation under combined iron and temperature stress. The global impacts of these temperature-dependent changes to AOA iron demands were assessed using sensitivity experiments with a state-of-the-art biogeochemical model. Simulations showed that impacts on nitrification were concentrated at higher latitudes, but the alterations to ammonia concentrations were redistributed toward lower latitudes by mode and intermediate water transport. These findings reveal a previously unrecognized mechanism by which ocean warming may alleviate iron limitation of AOA, enhance their ecological competitiveness, and reshape ocean nitrogen cycling throughout marine ecosystems.